Dynamics of pro and anti-inflammatory cytokines in the early period of dental implantation. Part I (Эндодонтия Today)
Dynamics and proportions of proinflammatory and anti-inflammatory cytokines in patients with dental implantation were studied. In 106 patients with dental implants without complications, the study was performed before and after 7-10, 30 days. IL-1β, IL-6, TNF-α, IFN-γ, IL-4, IL-10 were determined in the gingival fluid by solid-phase enzyme immunoassay. A significant increase in the level of TNF-α and IL-10 was observed on day 7-10, and TNF-α at day 30. At 7-10 days after implantation, an imbalance in the ratio of IL-1β / IL-10, TNF-α / IL-4, TNF-α / IL-10 was observed in comparison with the control, the proportion of pro- and anti-inflammatory cytokines was almost normalized on day 30, Only the ratio of TNF-α / IL-10 remained elevated. The enhanced synthesis of pro-inflammatory cytokines was countered by the enhanced synthesis of IL-10, which in our opinion is related to the ability of IL-10 to inhibit the cytotoxic activity that TNF-α exerts.